2014
DOI: 10.3109/08820538.2013.874489
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler Imaging of the Orbital Vessels in Ankylosing Spondylitis

Abstract: This result suggests no possible contributory role of vascular structures in formation of uveitis in AS. We believe that our preliminary results need to be complemented with further studies, particularly including AS patients with uveitis and rheumatic diseases with other ocular involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In one study conducted on patients with ankylosing spondylitis, no significant differences in ocular blood flow were detected between the patient group and the control group; however, the authors commented that a large proportion of the patients were using disease-modifying anti-rheumatic drugs, which could have affected the results of the measurements. 28 For our study, we selected patients who had not received systemic treatments, in order to avoid such a bias. Eye involvement in psoriasis is a recent subject of interest, which has been studied in the past few years by various authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study conducted on patients with ankylosing spondylitis, no significant differences in ocular blood flow were detected between the patient group and the control group; however, the authors commented that a large proportion of the patients were using disease-modifying anti-rheumatic drugs, which could have affected the results of the measurements. 28 For our study, we selected patients who had not received systemic treatments, in order to avoid such a bias. Eye involvement in psoriasis is a recent subject of interest, which has been studied in the past few years by various authors.…”
Section: Discussionmentioning
confidence: 99%
“…Such a theory may also be proposed for psoriasis, in which the carotid artery IMT is also increased. In one study conducted on patients with ankylosing spondylitis, no significant differences in ocular blood flow were detected between the patient group and the control group; however, the authors commented that a large proportion of the patients were using disease‐modifying anti‐rheumatic drugs, which could have affected the results of the measurements . For our study, we selected patients who had not received systemic treatments, in order to avoid such a bias.…”
Section: Discussionmentioning
confidence: 99%
“…The most important result of our study is that the mean velocity, resistive index, and volume measurements of the patients with AS were significantly higher than those of the controls. In a similar study by Ozsahin et al [ 10 ], no significant difference was found between the two groups in terms of Doppler parameters However, the authors did not include patients with AU in their sample. Two important differences of our study from this study are the differences in the Doppler findings of patients with AS and the normal population, and the inclusion of patients with AU in our study.…”
Section: Discussionmentioning
confidence: 91%
“…The most important feature that makes our study unique is that it is the first study in which positive findings were published in patients with AS. Negative results were reported in the only study on this subject in the literature [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation